1993
DOI: 10.1093/oxfordjournals.aje.a116854
|View full text |Cite
|
Sign up to set email alerts
|

Composite Risk Score for Kaposi's Sarcoma Based on a Case-Control and Longitudinal Study in the Multicenter AIDS Cohort Study (MACS) Population

Abstract: The possibility that an agent in addition to human immunodeficiency virus type 1 may be involved in the etiology of Kaposi's sarcoma in acquired immunodeficiency syndrome (AIDS) patients was investigated between 1984 and 1992 in this nested case-control analysis from the Multicenter AIDS Cohort Study (MACS) of homosexual and bisexual men. A total of 316 cases of Kaposi's sarcoma were identified and compared with 510 participants with AIDS and no evidence of cancer. More of the Kaposi's sarcoma cases were from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…What is less clear is why the associations of syphilis and HIV with HHV-8 do not extend as clearly to other STDs, which were also common in this population [14]. KS and HHV-8 infection in men have been linked to STDs, particularly syphilis [10,15,16]. Smith and colleagues [17] recently reported that heterosexual sex was not a mode of HHV-8 transmission in a large cohort of adults attending an STD clinic in Great Britain.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…What is less clear is why the associations of syphilis and HIV with HHV-8 do not extend as clearly to other STDs, which were also common in this population [14]. KS and HHV-8 infection in men have been linked to STDs, particularly syphilis [10,15,16]. Smith and colleagues [17] recently reported that heterosexual sex was not a mode of HHV-8 transmission in a large cohort of adults attending an STD clinic in Great Britain.…”
Section: Discussionmentioning
confidence: 90%
“…Among Africans and homosexual men, the risk of KS and/or HHV-8 infection is variably associated with specific behaviors, such as a large number of lifetime sex partners [8,9], rectal intercourse [10], and oral-anal contact [11]. In our study, lifetime number of male sex partners was statistically associated with HHV-8 infection among HIV-infected women, a finding that did not extend to the HIV-uninfected study participants (perhaps due to a smaller sample size).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggested that some cofactor highly associated with gay lifestyle was operating in conjunction with HIV in the pathogenesis of AIDS-related KS. Nitrite inhalants were suggested as one possible factor (10,11,(51)(52)(53)(54)(55)(56).…”
Section: History and Clinical Usesmentioning
confidence: 99%
“…Nitrite inhalants are used more commonly by gay men than others (6); use has been declining since AIDS was first reported (30) and has roughly paralleled the pattern of reported KS cases, and use among whites is greater than among blacks, as is the incidence of KS (22). Second, some, but not all, epidemiologic studies have shown a statistical association between the development of KS among gay men with AIDS and the use of large quantities of nitrite inhalants when compared with gay men with AIDS, but without KS (11,(51)(52)(53)(54)(55)(56). Third, anecdotal reports of increased frequency of AIDS-related KS on the chest and face, especially the nose, and in the lungs are consistent with the body areas most heavily exposed to nitrite vapors when inhaled.…”
Section: History and Clinical Usesmentioning
confidence: 99%
“…This unique distribution has led to the hypothesis that a sexually transmitted factor is involved. Geographical factors, coexisting sexually transmitted infections, recreational drugs like nitrates and the number of sexual partners are factors influencing the frequency of EKS [2,9]. Although the proportion of homosexual and bi sexual patients developing EKS until death remained constant, the incidence of EKS as the primary AIDS manifestation decreased [30], Tírese data suggest the increasing manifesta tion of EKS in more advanced stages of HIV-infection as a second or third AIDS event.…”
mentioning
confidence: 99%